Effects of EGCG on depression-related behavior and serotonin concentration in a rat model of chronic unpredictable mild stress. Issue 10 (21st September 2020) - Li, Guangjian; Yang, Jing; Wang, Xu; Zhou, Chen; Zheng, Xiangyu; Lin, Weihong
Abstract : The aim of this study is to examine the antidepressant-like effect of EGCG and get deeper insights into implications of modulating serotonin (5-HT) in the colon and brain. Abstract : The aim of this study is to examine the antidepressant-like effect of EGCG and get deeper insights into implications of modulating serotonin (5-HT) in the colon and brain. A total of 24 stochastically-selected rats were subdivided into three groups: one group served as the control group, and other two groups were subjected to chronic unpredictable mild stress interventions (CUMS group and CUMS + EGCG group respectively). Before conducting a designed set of behavior tests, all rats were weighed and then forced swimming test (FST) and open field test (OPT) were performed in all rats for the measurement and analysis of central and colonic serotonin levels. In order to determine the extent of CUMS-induced injuries and examine neurological deficits, the method of Nissl staining was implemented accordingly. Meanwhile, haematoxylin-eosin (H&E) staining was employed to detect the structure of the colon. The study found that, due to the involvement of CUMS, the body weight of experimental rats declined, their time of immobility in FST was greater, and the avoidance of central sections in OPT was also greater and more obvious. However, through intervention of the EGCG treatment, either weight loss or depression-related behavior induced by the involvement of CUMS was alleviated in the experimental rats. Comparison of both CUMS and CUMS + EGCG groups indicated that EGCG administration may decrease the level of serotonin (5-HT) in the colon but increase the level of serotonin (5-HT) in the hippocampus. However, it should be noted that the level of 5-HT in peripheral blood did not show any significant difference between both groups. Furthermore, CUMS caused the morphological changes of the hippocampus and structural changes of the colon were noteworthy. Summarily, the investigation results of this experimental study indicated that the intervention of EGCG treatment might have considerable implications in several aspects such as anti-depression, regulation of 5-HT concentration, enhancement of intestinal hyper-permeability, and neuroprotection in the hippocampus.